2017
DOI: 10.1128/aem.00653-17
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Neutral Electrolyzed Water for Inactivation of Human Norovirus

Abstract: Human norovirus (NoV) is the leading cause of acute gastroenteritis worldwide. Persistence on surfaces and resistance to many conventional disinfectants contribute to widespread transmission of norovirus. We examined the efficacy of neutral electrolyzed water (NEW; pH 7) for inactivation of human NoV GII.4 Sydney in suspension (ASTM method 1052-11) and on stainless steel surfaces (ASTM method 1053-11) with and without an additional soil load. The impact of the disinfectant on viral capsid was assessed using re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 30 publications
1
29
0
Order By: Relevance
“…Residual soil (organic) load in the working suspensions was approximately 2·5% as previously reported (Moorman et al . 2017). Samples obtained from two different naturally infected individuals were used in this study, both with initial titres of 6–7 log 10 GEC per ml.…”
Section: Methodsmentioning
confidence: 99%
“…Residual soil (organic) load in the working suspensions was approximately 2·5% as previously reported (Moorman et al . 2017). Samples obtained from two different naturally infected individuals were used in this study, both with initial titres of 6–7 log 10 GEC per ml.…”
Section: Methodsmentioning
confidence: 99%
“…American Society for Testing and Materials (ASTM) method E1052-11 [16] was followed for disinfection suspension assays with minor modifications to account for reduced testing volume [10] : 60 µL HuNoV fecal suspensions (PBS or SGF) was suspended into 540 µL of each one of the disinfectants according to manufacturer's instructions. Disinfectant activity was neutralized by transferring 60 µL of HuNoV/disinfectant mixture into 540 µL 10% Dey/Engley neutralizing broth (D/E), (BD Difco, Sparks, MD).…”
Section: Methodsmentioning
confidence: 99%
“…In the disinfection studies, HuNoV inactivation was calculated as previously described by subtracting log 10 genomic copy number of treatment samples from the genomic copy number of the corresponding neutralization control sample [10] . In case of samples yielding non-detection via RT-qPCR analysis, HuNoV inactivation was calculated by subtracting the assay limit of detection value (1.18 log 10 genome copies) from the corresponding log 10 neutralization control values.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies (4,15,23) reported the effectiveness of EW with HOCl concentrations as low as 100 ppm against SARS-CoV-2, and many HOCl-based products have been developed that meet the EPA criteria for use against SARS-CoV-2 (5). Moreover, previous studies (24,25) showed that slightly acidic EW and neutral EW generated in single-cell units (without diaphragm), similar to that mentioned in this report, were effective against difficult-to-kill viruses/pathogens (such as non-enveloped viruses (e.g., norovirus) (26). However, the rapid viricidal effect of any EW disinfectant depends on the FAC (specifically HOCl) concentration; at a lower FAC (such as in old solutions that have been in contact with the atmosphere for a long period), the disinfectant ability of the solution is lost and the EW can no longer effectively inactivate SARS-CoV-2 (4).…”
Section: Reportmentioning
confidence: 98%